Empowerment of Small and Medium-Sized Tofu Factory Enterprises Through Brand Logo Creation and Processing of Tofu Residue into Nuggets - Anastasyia Hilda Fahriza; Nadiva Aulia Yasmin; Raden Ajeng Sayyidatina Qur'aniyah; Rifki Warri Zain; Kukuh Wisnuaji Anjasmoro; Riki Hanggara (Jurnal Masyarakat Religius dan Berwawasan, 2023)
Every region in Indonesia has different potentials and allows it to be developed in various fields, one of which is the business in Saptorenggo Village, RT 04 RW 04, Pakis, Malang Regency. In this village, a very good business is to be developed, namely the development of Mrs Wiwit's tofu factory. The development focuses on creating brands and logos and utilizing tofu waste in new products. Mrs Wiwit's tofu factory business does not yet have a patented name to use or a logo on the product to increase its marketing in online and offline markets. Brand names and logos for SMEs are powerful factors for marketing these products to areas outside the village. Utilization of tofu waste can also be considered not optimal other than being disposed of in its place; tofu waste is usually sold to villagers for animal feed. The tofu dregs are our focus in processing new products for greater selling value. In addition, developing the resulting product can open up opportunities to develop human resources in this new business. Utilization of tofu waste is processed into a new product in the form of a Nugget made with a mixture of tofu dregs that are no longer used.